Identification of an SCPL Gene Controlling Anthocyanin Acylation in Carrot (Daucus carota L.) Root - Curaba, Julien; Bostan, Hamed; Cavagnaro, Pablo F.; Senalik, Douglas; Mengist, Molla Fentie; Zhao, Yunyang; Simon, Philipp W.; Iorizzo, Massimo (Frontiers in Plant Science, 2020)
Anthocyanins are natural health promoting pigments that can be produced in large quantities in some purple carrot cultivars. Decoration patterns of anthocyanins, such as acylation, can greatly influence their stability and biological properties and use in the food industry as nutraceuticals and natural colorants. Despite recent advances made towards understanding the genetic control of anthocyanin accumulation in purple carrot, the genetic mechanism controlling acylation of anthocyanin in carrot root have not been studied yet. In the present study, we performed fine mapping combined with gene expression analyses (RNA-Seq and RT-qPCR) to identify the genetic factor conditioning the accumulation of non-acylated (Cy3XGG) versus acylated (Cy3XFGG and Cy3XSGG) cyanidin derivatives, in three carrot populations. Segregation and mapping analysis pointed to a single gene with dominant effect controlling anthocyanin acylation in the root, located in a 576kb region containing 29 predicted genes. Orthologous and phylogenetic analyses enabled the identification of a cluster of three SCPL-acyltransferases coding genes within this region. Comparative transcriptome analysis indicated that only one of these three genes, DcSCPL1, was always expressed in association with anthocyanin pigmentation in the root and was co-expressed with DcMYB7, a gene known to activate anthocyanin biosynthetic genes in carrot. DcSCPL1 sequence analysis, in root tissue containing a low level of acylated anthocyanins, demonstrated the presence of an insertion causing an abnormal splicing of the 3rd exon during mRNA editing, likely resulting in the production of a non-functional acyltransferase and explaining the reduced acylation phenotype. This study provides strong linkage-mapping and functional evidences for the candidacy of DcSCPL1 as a primary regulator of anthocyanin acylation in carrot storage root.